Analisa Perwujudan PSAP No.7 Akuntansi Aset Tetap pada PTN X Kota Surabaya - Ramadhani, Sabina Fitri; Azmiyanti, Rizdina (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The aim of this study is to evaluate the implementation of PSAP No.7 regarding the accounting treatment of fixed assets at PTN.X Surabaya. This research applies qualitative techniques, where interviews are carried out and inventory reports are carried out. The research output shows that the measurement and recognition of fixed assets at PTN.X is in line with PSAP No.07. This can be seen from the fixed assets owned by PTN.X, such as land, tools and machines, which have a useful life of 12 months. The costs of acquiring assets at PTN.X can be calculated reliably and supported by authentic evidence that the buildings and structures are the official property of PTN.X through a descriptive approach.